Biomethane in Domestic and Industrial Applications - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. This chapter is concerned with substituting biomethane in situations where LPG fossil fuel is normally used. In many parts of the world, domestic stoves use liquid petroleum gas (LPG), supplied in portable tanks. LPG is a gas that has been liquefied in storage and consists of 60% propane and 40% butane. It is also used in transportation and agricultural applications. In industries, such as ceramic making, many firing kilns also use LPG. If biomethane is to be used as a LPG replacement then methods of (a) biomethane storage and (b) stove/furnace modification to allow biomethane combustion are required. This chapter will outline a solution to both of these hurdles. Upgrading plants to produce biomethane was discussed in Chap. 3. In this chapter, a storage and delivery solution will be discussed and a methodology was developed and implemented for converting stoves and industrial furnaces for biomethane use. Biomethane can be produced, delivered, and combusted safely and efficiently in LPG-powered applications.